2005
DOI: 10.1007/s11010-005-8215-2
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic effect of nickel compounds

Abstract: Nickel is a widely distributed metal that is industrially applied in many forms. Accumulated epidemiological evidence confirms that exposures to nickel compounds are associated with increased nasal and lung cancer incidence, both in mostly occupational exposures. Although the molecular mechanisms by which nickel compounds cause cancer are still under intense investigation, the carcinogenic actions of nickel compounds are thought to involve oxidative stress, genomic DNA damage, epigenetic effects, and the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(127 citation statements)
references
References 222 publications
5
117
0
5
Order By: Relevance
“…These synergistic epigenetic effects are further corroborated by statistically significant reduction of H3-Ser10 phosphorylation caused by tungsten-alloy as compared to cobalt concentration (CoA) equivalent to the percentage that was used in the preparation of tungsten-alloy in C2C12 cells. When cobalt and tungsten carbide particles are in close contact, the generation of reactive oxygen species may take place, disturbing signaling pathways involved in proliferation, apoptosis, transformation, and senescence (Lison et al, 1995;Lu, et al, 2005). Tungsten carbide-cobalt mixture has been shown to trigger DNA fragmentation and rearrangements of nucleosome/chromatin assembly in human peripheral blood mononucleated cells thus contributing to apoptosis (Lombaert et al, 2004(Lombaert et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…These synergistic epigenetic effects are further corroborated by statistically significant reduction of H3-Ser10 phosphorylation caused by tungsten-alloy as compared to cobalt concentration (CoA) equivalent to the percentage that was used in the preparation of tungsten-alloy in C2C12 cells. When cobalt and tungsten carbide particles are in close contact, the generation of reactive oxygen species may take place, disturbing signaling pathways involved in proliferation, apoptosis, transformation, and senescence (Lison et al, 1995;Lu, et al, 2005). Tungsten carbide-cobalt mixture has been shown to trigger DNA fragmentation and rearrangements of nucleosome/chromatin assembly in human peripheral blood mononucleated cells thus contributing to apoptosis (Lombaert et al, 2004(Lombaert et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The causality between nickel exposure and cancer development has been supported by both animal studies and epidemiologic investigations (2). It was reported that both the genetic and epigenetic factors were attributable to the carcinogenic characteristics of mode of action for nickel (3,4). Induction of hypoxia-inducible factor-1␣ (HIF-1␣) 3 by nickel treatment was documented both in vivo and in vitro (5).…”
mentioning
confidence: 99%
“…Water soluble nickel salts are taken up only slowly by cells, while particulate of nickel compounds are phagocytosed and, due to the low pH, gradually dissolved in lysosomes, yielding high concentrations of nickel ions in the nucleus . Using in vitro cells and animal models, nickel compounds have been found to generate various types of adverse effects, including chromosomal aberrations, DNA strand breaks, high reactive oxygen species production, impaired DNA repair, hypoxia-mimic stress, aberrant epigenetic changes, and signaling cascade activation (Lu et al, 2005). Nickel has been shown to interfere with the repair mechanisms involved in removing UV-, platinum-, mitomycin C, g-radiation-and benzo[a]pyrene-induced DNA damage (Dally et al, 1997;Hartmann et al, 1998;Schwerdtle et al, 2002).…”
Section: Nickelmentioning
confidence: 99%